BUDAYA LOKAL : MODAL HIDUP BERAGAMA DAN BERMASYARAKAT - Fabianus Selatang; Yuliana Eni Yuliati; Maria Vianti Desa; Maria Dara Sintani (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2022)
Diversity in culture, ethnicity, language is not only a wealth or treasure in living together, but can also threaten unity, harmony and harmony. Conflicts between cultures, ethnicities and languages ​​often occur in social life. This had a negative impact not only on inter-ethnic life, but also on religious life. The purpose of this research is to examine the threat aspects of cultural diversity, as an opportunity to build and strengthen a sense of brotherhood, love for one another and uphold mutual respect and respect for differences as a capital of religious and social life by students of SMAK Bhakti Luhur Malang. The method used by researchers is a qualitative method. Researchers use a descriptive approach. Data sources are students of grades 1, II and III. The researcher chose 3 students as representatives of the population. In addition, data was also taken from teachers and school principals. The technique of determining informants uses purposive sampling technique. Researchers also refer to research results that have been published in national journals in order to map the novelty of this research. The data collection technique is an open interview. The instrument used by the researcher is a list of questions. The analysis technique goes through three stages namely reduction, display and data verification. The author concludes that tensions and conflicts are caused by low understanding and awareness in responding to differences in ethnicity, language and culture. Development of local culture in schools as a constructive step in developing religious values. Therefore, it is necessary to revive local cultural values ​​as a living laboratory for students so that they can be used as a basis for developing an attitude of religious moderation in the wider community.